Control and stabilization of grid-connected converters operating as constant power load in a smart transformer grid scenario - Zhang, Chi; Buticchi, Giampaolo; Yang, Jiajun; Zou, Zhixiang (2020)
The development of power electronics and control technology provides improved performance of the electrical appliances, making them robust to changes in the supply voltage or frequency. However, power electronic converters behave as constant power loads (CPLs), which have negative impedance characteristics, and this non-linear behavior is challenging the stability of the grid. This paper investigates the input impedance of a three-phase low-voltage grid connected ac-dc converter that operating as a CPL when interfaced to a single DC bus and a changeable load. The possibility of adopting a Smart Transformer (ST), a power electronics converter which feeds a low-voltage grid, for the CPL stabilization is also addressed. To analyze the behavior of CPLs, a strategy of impedance modelling is employed. Gain Margin Phase Margin (GMPM) Criterion is referred to judge the stability of the system and verify the stabilization operation for CPLs. Simulation results are presented to be as a support.